(untitled) (Global Journal of Human-Social Science, 2013)
The objective of this research was to analyse repercussions on instructional design and teaching when integrating mobile devices with virtual learning environments. The study was conducted in a graduate program, at a university in Mexico offering distance programs. The methodology followed was exploratory and descriptive, conducting open interviews with faculty, program directors, and educational and innovation technology directors to explore two units of analysis: mobile learning devices and virtual environments. From the results obtained, it became evident that working with mobile devices in virtual environments has repercu-ssions at different levels: organizational, structural, social, technological, ways of thinking and actions. These results contribute information concerning the integration of new generation devices to virtual environments and may lead to future studies.